Brachial endothelial function and carotid intima-media thickness in patients with coronary artery disease - Mahdavi-Roshan, Marjan; Salari, Arsalan; Nasrollah zadeh, Javad; Doostdar-Sanaye, Mehrnaz (Archives of Advances in Biosciences, 2015)
Endothelial dysfunction and carotid intima-media thickness are 2 indicators of subclinical cardiovascular disease. The aim of study was to analyze brachial flow mediated dilation(FMD)and carotid intima media thickness (CIMT)in patients with coronary artery disease, and investigate the relationship between endothelial function, CIMT and coronary artery disease risk factors.56 men and women aged between 25 to 75 years with coronary artery disease were recruited. FMD and CIMT was measured by B-mode ultrasonography. Data were presented as mean ± SE. Pearson correlation coefficients were used to evaluate associations and T-test and Chi-square tests were used for quantitative and qualitative variables. P-values < 0.05 were considered to indicate statistically significant differences. The mean age of subjects was 59.37±1.28 years. The frequencies of one, two and three-vessel coronary artery disease were 61%, 35.1% and 3.9%, respectively. The mean of CIMT in patients was 0.79±0.02 mm, and 65.5% of patients had CIMT more than 0.8 mm.The mean of FMD was 4.79±0.55% and 65.4% of patients had FMD lower than 5.3%. CIMT was correlated directly with number of diseased vessels, age andtotal cholesterol and was correlated inversely with HDL-C.Non-invasive measurement of FMD and CIMT are interrelated techniques that probably assess the same atherosclerotic process from functional and anatomic viewpoints.In these patients an increase in CIMT and decrease in FMD may warrant more aggressive risk factor control through the beginning of effective medical treatment.